Vulnerability detection and prevention of SQL injection - J. Santhosh Kumar, B; P. Anaswara, P (International Journal of Engineering and Technology, 2018)
SQL injection attack is the most serious security vulnerabilities on databases are connected with web or within an intranet, most of these vulnerabilities are affected by lack of input validation and SQL parameters are use. The attackers are trying to steal the data which was hidden and by attacking the database using the attacking technique that is called SQL injection attacks. The SQL injection attack detection and prevention technologies are experimented in this paper. There are different defence methods are used to prevent such as, parameterized statement, stored procedures and white list input validation. The comparative results of these methods are highlighted in the table with SQL injection query, prepared statement insertion and selection queries, stored procedures and modify queries. The comparison of these methods used for detection and prevention vulnerability in web server.Â Â